Pengaruh Hypnobirthing Terhadap Nyeri Persalinan Pada Ibu Inpartu Kala I - Treasa, Adisty Dwi; Nurhaedah, Nurhaedah; Wijayanti, Lumastari Ajeng; Purbanova, Reni (Barongko: Jurnal Ilmu Kesehatan, 2025)
Labor pain is a physiological process that can cause anxiety and stress in mothers in labor. Hypnobirthing is a relaxation method that aims to reduce fear and pain during labor. This study aims to determine the effect of hypnobirthing on the level of labor pain in mothers in the first stage of labor. The research method used was a quasi-experimental method with a pretest-posttest control group design approach. The sample consisted of 30 mothers in labor who were divided into two groups, namely the intervention group given hypnobirthing and the control group who received standard care. The instrument used was the Visual Analog Scale (VAS). The results showed that there was a significant difference in the level of pain between the intervention and control groups (p <0.05). The conclusion of this study is that hypnobirthing is effective in reducing labor pain in mothers in the first stage of labor. It is expected that hypnobirthing can be one of the non-pharmacological methods applied in midwifery care.